2016
DOI: 10.7554/elife.16096
|View full text |Cite
|
Sign up to set email alerts
|

The composition and organization of Drosophila heterochromatin are heterogeneous and dynamic

Abstract: Heterochromatin is enriched for specific epigenetic factors including Heterochromatin Protein 1a (HP1a), and is essential for many organismal functions. To elucidate heterochromatin organization and regulation, we purified Drosophila melanogaster HP1a interactors, and performed a genome-wide RNAi screen to identify genes that impact HP1a levels or localization. The majority of the over four hundred putative HP1a interactors and regulators identified were previously unknown. We found that 13 of 16 tested candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 168 publications
1
75
0
Order By: Relevance
“…However the mechanisms linking these silencing pathways are not fully understood and it is clear that factors involved in heterochromatin formation and function remain to be identified. For example a recent study of HP1a interactors in Drosophila identified many new factors needed for gene silencing and/or heterochromatin organization (73)…”
Section: Discussionmentioning
confidence: 99%
“…However the mechanisms linking these silencing pathways are not fully understood and it is clear that factors involved in heterochromatin formation and function remain to be identified. For example a recent study of HP1a interactors in Drosophila identified many new factors needed for gene silencing and/or heterochromatin organization (73)…”
Section: Discussionmentioning
confidence: 99%
“…XNP lacks the C-terminal plant homeodomain (PHD) fingers that are present in ATRX and that mediate ATRX binding to chromatin. In Drosophila, interaction with chromatin is achieved by a separate protein, called dADD1 (32). Mass spectrometry analysis revealed that dADD1, similarly to XNP, was not found among the proteins present in the immunopurified H3.3 complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Our work raises questions 443 about the biological significance of SUUR binding to heterochromatin, since without the SNF2 444 domain SUUR is still constitutively bound to heterochromatin, yet unable to induce 445 underreplication. Additionally, SUUR dynamically associates with heterochromatin in mitotic 446 cells although heterochromatin is fully replicated (Swenson et al, 2016). 447 448…”
Section: Snf2 Domain and Fork Localization 420mentioning
confidence: 99%